Thymolipoma: a report of nine cases, with emphasis on its association with myasthenia gravis - Rieker, Ralf Joachim; Schirmacher, Peter; Schnabel, Philipp Albert; Moser, Katharina; Hoffmann, Hans; Dienemann, Hendrik; Pfannschmidt, Joachim (Surgery today, 2010)
Thymolipomas are rare tumors of the anterior mediastinum accounting for up to 9% of all thymic tumors. These tumors are associated with autoimmune diseases in up to 50% of the patients, including myasthenia gravis, aplastic anemia, hypogammaglobulinemia, lichen planus, and Graves’ disease. These tumors with a fatty appearance also can arise in older patients with autoimmune disease.